The Values of Islamic Education In Transformation of The Megengan Show Tradition In Jajar, Gandusari, Trenggalek - Asna, Ni'am Khurotul; Abdul Aziz; Akhyak; Salma Azizah Wifaqi; Ismail, Ahmad Nur Ismail (MultiTech Publisher, 2024)
The tradition of the slametan megengan show by the Islamic Javanese people has undergone innovation and modification. The megengan transformation carried out in Jajar Village, Gandusari District, Trenggalek Regency has combined old ritual processions with modern local art typical of the Jajar Village community. Megengan show is rich in important values ​​including its relation to the values ​​of Islamic education. The transformation phenomenon of the megengan show tradition lies in its form and implementation in order to dissect existing noble values ​​so that it becomes good teaching in the community as well as an effort to preserve local traditions and culture. The aim of this research is to discover and describe the values ​​of Islamic education in the megengan show tradition. This research uses a phenomenological approach to a case study type of research. The data source for this research uses primary data obtained through interviews, observation and documentation. The results of research regarding the values ​​of Islamic education in the transformation of the megengan show include the value of worship, the value of charity (ihsan), the value of trust, the value of the future, and the value of da'wah.